Bilateral ascending uterine arteries ligation for conservative management of complete placenta previa: three case reports - K. Relakis; A. Pontikaki; I. Kosmas; S. Sifakis (IMR Press, 2020)
Placenta previa (PP) is considered one of the major causes of both antepartum and intrapartum bleeding, which necessitates preterm delivery typically by cesarean section. The optimal management is controversial. Surgical techniques to control severe bleeding after placental removal include uterine/internal iliac artery ligation, compression sutures, and embolization of pelvic vessels; however, cesarean hysterectomy remains the ultimate rescue procedure for uncontrolled maternal hemorrhage. The authors present a modified surgical technique of the uterine arteries ligation for successful management of complete PP. The method was effective and hysterectomy was avoided in all cases. Serious complications such as hypovolemic shock, disseminated intravascular coagulopathy, urinary tract injuries, febrile infections, and uterine necrosis were not recorded. Double bilateral ligation of the ascending uterine arteries before placental removal constitutes a prophylactic method that prevents postpartum hemorrhage and emergency obstetric hysterectomy. This method has an additional advantage as if it proves ineffective for hemorrhage control, the basic steps for cesarean hysterectomy would have been done.